(untitled) (Revista Argentina de Cirugía, 2021)
Peritoneal adhesions produced as a consequence of manual or instrumental manipulation during surgery cause bowel obstruction. Several procedures have been developed to avoid or minimize adhesions. Mesenteric plication with temporary suture support organizes the healing process in the bowel in case of high suspicion of adhesions will develop, particularly when bowel obstruction is produced by adhesions. The basis of this technique is the same as for standard procedures and, thus, there are no controversies about its indications. The rationale of temporary suture support is that when the healing process is over, about two weeks after the intervention, the suture support is no longer needed. We report three cases of intestinal obstruction undergoing mesenteric plication and temporary suture support, with favorable outcomes.